IP location - Dawson, Martin (McGraw-Hill, 2007)
In today's vast world of global commerce with users that are more nomadic than ever, the need for reliable, secure, and efficient access technologies is rapidly increasing. IP Location provides you with a guided tour of location determination, tackling this new technology head on and addressing all aspects of location management, delivery, and conveyance within IP networks. Covering important real-world applications such as emergency (911) services, asset tracking, call routing, navigation, and staff location in hot desk environments, this book gives you all the information you need to fully support this cutting-edge technology